Analisis dan Identifikasi Hygiene Factors dan Pengaruhnya terhadap Kepuasan Kerja pada Mitra Kerja PT. PLN UIP Nusa Tenggara - Suryani, Embun; Wahyulina, Sri; Hidayati, Siti Aisyah (LPPM Universitas Mataram, 2020)
This study aims to identifyÃ‚Â hygiene factorsÃ‚Â and analyze their effects on job satisfaction. The data collection method in this study is a survey method, using aÃ‚Â questionnaireÃ‚Â as a data collection tool. The population in this study were all employees at the staff level and executors/non-staff of PT. PLN UIP Nusra consists of PT. PP Wartsila, PT. Hydro Techno Utama, and PT. Purnama Indonesia. Employees at the staff and executive/non-staff level are 75 people. At the same time, the determination of the sample is done by usingÃ‚Â accidental samplingÃ‚Â method with a total sample of 50 people. The research variables consist of independent variables in the form of dimensions ofÃ‚Â hygiene factorsÃ‚Â and the dependent variable in the form of job satisfaction. Data analysis procedures in this study were divided into three stages, namely: 1) Conducting anÃ‚Â importance-performance; 2) analysisÃ‚Â (IPA) on the dimensions ofÃ‚Â hygiene factorsConducting analysisÃ‚Â CrosstabsÃ‚Â (cross table); 3) Conducting multiple regression analyzes. The results of data analysis showed that overall the quality performance of the dimensionÃ‚Â hygiene factorsÃ‚Â was in a proper category. Then, an analysis of the level of employee job satisfaction shows that the employees of PT. PLN UIP Nusra shows job satisfaction. Meanwhile, the results of multiple linear regression analysis showed that the variableÃ‚Â hygiene factorsÃ‚Â andÃ‚Â motivating factorsÃ‚Â had a positive and significant effect on the level of employee job satisfaction at PT. PLN UIP Nusra